EFFICIENCY OF INTRAVASCULAR LASER BLOOD IRRADIATION IN CATTLE WITH INFLAMMATORY SURGICAL PATHOLOGY - Kulynych, S.M.; Bublyk, O.O.; Yurchenko, I.I.; Панасова, Т.Г.; Kravchenko, S.O.; Lockes-Krupka, T.P. (World of Medicine and Biology, 2019)
The laboratory studies results of intravascular laser blood irradiation (ILBI) influence on the bodies of bulls, subjected to jugular veins resection and castration, and cows with papillomatous dermatitis in the area of fingers are presented. After ILBI application similar changes in blood serum of experimental animals were established for different pathological processes. The tendency of ASAT, AP activity and C-reactive protein amount reducing to the norm was revealed, indices growth of non-specific immunological reactivity: serum BSBA and BSLA and opsono-phagocytic activity of blood neutrophils was determined. In the experimental group bulls, one or two days earlier the wound healing and the absence of tissue edema around the affected areas were observed.